FEASIBILITY ANALYSIS OF SMALL MEDIUM ENTERPRISES (MSMEs) IN MANDAILING NATAL REGENCY IN ACCESSING FINANCING IN SHARIA BANK - suci suci; fatahuddin siregar; sarmiana batubara; sry lestari (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The background of this research is Micro, Small and Medium Enterprises (MSMEs), which are productive businesses owned by individuals or private business entities, also called populist businesses, which currently receive attention and privileges mandated by law, including business credit assistance with low interest, ease of business permit requirements, business development assistance from government agencies, and several other facilities. No exception in Mandailing Natal Regency, which on average has a Micro, Small and Medium Enterprises (MSMEs). Lack of a good management system and capital that causes the failure of Micro, Small and Medium Enterprises (MSMEs) in Mandailing Natal Regency. The analysis is used to determine whether Micro, Small and Medium Enterprises (MSMEs) are eligible in obtaining financing from Bank Syariah Mandiri KCP Panyabungan. This research is a descriptive qualitative research. Data collection techniques in this study were interviews, observation, and documentation. The research subjects in this study consisted of First Informants namely SMEs and Secondary Informants namely Bank Mandiri Sharia Panyabungan KCP. The results of the study can be seen that the micro financing of Bank Syari'ah Mandiri is an alternative financing product from Bank Syari'ah Mandiri which is intended for MSME entrepreneurs (Micro, Small and Medium Enterprises). Analysis of the feasibility of micro financing of the Syari'ah Bank Mandiri Panyabungan Sub-Branch Office to prospective customers is that the submission must meet the requirements: Character, Capacity, Capital, Collateral, Condition (5C) and the conditions that must be met by the SMEs. In accessing financing in Islamic banks is very influential because there must be requirements that must be completed so that the disbursement of financing for Micro, Small and Medium Enterprises (MSMEs) can be resolved as soon as possible and can be accepted by the bank.